2023
DOI: 10.1002/adma.202305151
|View full text |Cite
|
Sign up to set email alerts
|

High‐Load Gemcitabine Inorganic–Organic Hybrid Nanoparticles as an Image‐Guided Tumor‐Selective Drug‐Delivery System to Treat Pancreatic Cancer

Myrto Ischyropoulou,
Kristina Sabljo,
Leonie Schneider
et al.

Abstract: Pancreatic ductal adenocarcinoma (PDAC) has a devastating prognosis without effective treatment options. Thus, there is an urgent need for more effective and safe therapies. Here, we present inorganic‐organic hybrid nanoparticles (GMP‐IOH‐NPs) as novel drug‐delivery system for the selective delivery of extraordinarily high concentrations of gemcitabine monophosphate (GMP) not only to the primary tumor but also to metastatic sites. GMP‐IOH‐NPs have a composition [ZrO]2+[GMP]2– with GMP as drug anion (76% of tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The inhibition of DNA replication by anti-cancer drug gemcitabine parallels the inhibition of CAFs and blocks the formation of tumor clusters in cells derived from lung metastases. Gemcitabine is an FDA-approved inhibitor of DNA replication and effectively kills cancer cells by increasing apoptosis [24][25][26]. We found that in a low-density setting, LM81 cells treated with gemcitabine (5 nM) do not form tumor clusters, compared to DMSO-treated cells (Figure 9A).…”
Section: Resultsmentioning
confidence: 92%
“…The inhibition of DNA replication by anti-cancer drug gemcitabine parallels the inhibition of CAFs and blocks the formation of tumor clusters in cells derived from lung metastases. Gemcitabine is an FDA-approved inhibitor of DNA replication and effectively kills cancer cells by increasing apoptosis [24][25][26]. We found that in a low-density setting, LM81 cells treated with gemcitabine (5 nM) do not form tumor clusters, compared to DMSO-treated cells (Figure 9A).…”
Section: Resultsmentioning
confidence: 92%
“…We have observed similar intracellular localization patterns also for other, comparable types of nanocarriers, suggesting an endocytic internalization pathway with late endosomal/lysosomal localization after 24 and 48 h, respectively. 25 …”
Section: Resultsmentioning
confidence: 99%
“…To generate murine PDAC tumors, a quantity of 5 × 10 5 KPC cells was orthotopically implanted into the pancreatic head of C57BL/6 J mice, following previously established procedures 21 . Murine peripheral blood was collected from euthanized healthy C57BL/6J mice through cardiac puncture.…”
Section: Methodsmentioning
confidence: 99%